In Vitro Activity of MRX-8 and Comparators Against Clinical Isolated Gram-Negative Bacilli in China - Wu, Shi; Yin, Dandan; Zhi, Peiyuan; Guo, Yan; Yang, Yang; Zhu, Demei; Hu, Fupin (Frontiers in Cellular and Infection Microbiology, 2022)
To evaluate in vitro antibacterial activity of MRX-8 against gram-negative bacteria recently isolated from China, 765 clinical isolates were collected randomly from 2017 to 2020, including Enterobacterales and P. aeruginosa and A. baumannii, Stenotrophomonas maltophilia, Burkholderia cepacia, Alcaligenes app. and Haemophilus spp. isolates. All strains were performed with antimicrobial susceptibility testing by broth microdilution method according to the CLSI 2021. Antimicrobial agents included MRX-8, polymyxin B, colistin, amikacin, ceftriaxone, ceftazidime, cefepime, ceftazidime-avibactam, cefoperazone-sulbactam, meropenem, ciprofloxacin, ampicillin, ampicillin-sulbactam and levofloxacin. For carbapenem-susceptible and carbapenem-resistant E.coli isolates, the MIC50/90 of MRX-8 was 0.125/0.25 mg/L and 0.06/0.125 mg/L, respectively. For carbapenem-susceptible and carbapenem-resistant K. pneumoniae isolates, the MIC50/90 of MRX-8 was 0.25/0.5 mg/L and 0.125/0.5 mg/L, respectively. For polymyxins (polymyxin B and colistin)-resistant E. coli and K. pneumoniae, MIC50 of MRX-8 was 4-16 mg/L and MIC90 was >32 mg/L. The MIC50 and MIC90 of MRX-8 for other Klebsiella spp. except K. pneumoniae, Citrobacter spp., Salmonella spp. and Shigella spp. isolates ranged 0.06-0.125 mg/L and 0.06-0.25mg/L, respectively. For Morganella spp., Proteus spp., Providencia spp., Serratia spp., Stenotrophomonas maltophilia and Burkholderia cepacia, all MIC50 of MRX-8 was >32mg/L. For carbapenem susceptible and resistant P. aeruginosa, the MIC50 and MIC90 of MRX-8 was both 1mg/L, and that for A. baumannii was 0.5mg/L and 0.5-1mg/L. For Alcaligenes spp. and Haemophilus spp., MIC50/90 was 1/4 mg/L and 0.25/0.5 mg/L. MRX-8 was more effective against most clinically isolated gram-negative isolates, including carbapenem-resistant E. coli, K. pneumoniae, P. aeruginosa and A. baumannii, highlighting its potential as valuable therapeutics.